Pengaruh Beban Kerja dan Kompensasi terhadap Kinerja Karyawan di Butik Rumah Jahit Akhwat (RJA) Kota Makassar - Resi Ayumni Fajrin; Amrah Rachim; Ansar H. Mulkin Bas (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2026)
This study aims to examine the effect of workload and compensation on employee performance at Butik Rumah Jahit Akhwat (RJA) in Makassar City. The research employed a quantitative method with an associative approach to analyze the relationship between the independent variables and employee performance as the dependent variable. The population consisted of all employees working at Butik RJA, while the sample included 45 respondents selected using the Slovin formula. Primary data were collected through questionnaires distributed directly to the respondents. The data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that, partially, workload has a positive and statistically significant effect on employee performance, with a significance value of 0.027, which is lower than 0.05. In contrast, compensation has a positive but statistically insignificant effect on employee performance, with a significance value of 0.278, which exceeds 0.05. Simultaneously, workload and compensation have a significant effect on employee performance, indicating that both variables jointly contribute to improving employee performance at Butik Rumah Jahit Akhwat (RJA) Makassar City.